Crisis сommunication in social work during the war - Plakhova, Olena (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
The article analyzes the concepts of crisis and crisis communication in social work. The author notes the relevance of the need for the scientific development of algorithms and programs of crisis communications in social work during the war. Crisis communication in social work is defined as the establishment of sustainable interaction between local governments, civil society institutions, social institutions, churches, business representatives, and contact audiences (community residents, internally displaced persons, families of fallen soldiers, and other categories of victims of warfare) about existing problems and needs, their prompt resolution by all participants of the interaction. The following key properties of crisis communication in social work are identified by the author: flexibility and adaptability of methods of interaction between subjects; strengthening the informal means of reception and transmission of information; reduction of centralism in the communication process; promptness of the situational response to emerging problems. Crisis communication in social work is a sequence of actions that form a сеrtain communication strategy. The article determines the requirements for the development of a communication strategy during martial law in Ukraine and measures for its implementation, namely: identification of all possible contact audiences expecting information about further actions; reporting only verified and confirmed information; establishment of channels for receiving feedback from the contact audiences, as well as systematicity of two-way interaction of the subjects; assessment of the strengths and weaknesses of the communication activities carried out in order to avoid mistakes in crisis communication in the future. The author emphasizes that the crisis contains both potential threats and the danger of loss, as well as newrenewal and transformation opportunities for society, creating new modern approaches to interaction after a crisis period. Crisis phenomena in society will contribute to the emergence of new or modification of existing social practices, and cause a reaction to them from the public. As a result, new behavioral and communication practices and new subjects of interaction will emerge.